Lewin's Genes X - Krebs, Jocelyn E. Goldstein Elliott S. (Jones and Bartlett titles in biological science., 2011)
"The fields of molecular biology and molecular genetics are rapidly changing with new data acquired daily, and new insights into well-studied processes presented on a scale of weeks or months rather than years. For decades Lewin's GENES has provided the teaching community with the most cutting edge presentation of molecular biology and molecular genetics, covering gene structure, sequencing, organization, and expression. The latest edition, with a new author team, has enlisted 21 subject-matter experts, from top institutions, to provide revisions and content updates in their individual fields of expertise, ensuring that Lewin's GENES X is the most current and comprehensive text in the field. Informative new chapters, as well as a reorganization of material, provide the most logical flow of topics. Lewin's GENES X also contains new pedagogical features to help students learn as they read and an online student study guide allows students to test themselves on key material."--Jacket.